Penanaman Nilai-Nilai Karakter Hindu Dalam Tradisi Ngendar Di Banjar Sekarmukti Desa Pangsan - Perbowosari, Heny; Rudiadnyana, I Made (Jurnal Penelitian Agama Hindu, 2024)
The cultivation of character values is a very important matter in the development of a child's personality. Religious tradition is one way to teach the process of instilling character values in Hinduism. This is demonstrated by the Ngendar tradition in Sekarmukti Village, Pangsan Village, Badung Regency. The Ngendar tradition carried out by children in the Banjar Sekarmukti area, starts from H-2 Piodalan which is carried out on the day of Buda Umanis wuku Julungwangi or exactly 15 days before Galungan. The research approach is a naturalistic approach that answers research problems that require in-depth understanding and produces conclusions related to the Ngendar Tradition.  The Ngendar tradition during the piodalan at Penataran Agung Sekarmukti Temple in Petang Badung Bali carried out by children as a source of learning will encourage the appreciation of character values based on Hindu religious teachings. The cultivation of character values carried out in the Ngendar tradition includes (1) Gratitude (Ktajñatâ), (2) Maintaining Purity and cleanliness (Saucam), (3) Friendship (Maitri), and (4) Care. Broadly speaking, the implementation of this Ngendar tradition has a positive impact on children such as increasing sraddha and bhakti, growing a sense of solidarity and cooperation and creating discipline in children.